2023
DOI: 10.1021/acs.inorgchem.3c01224
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Functional Eu–Metal–Organic Framework with Ratiometric Fluorescent Broad-Spectrum Sensing of Benzophenone-like Ultraviolet Filters and High Proton Conduction

Abstract: The construction of attractive dual-functional lanthanide-based metal–organic frameworks (Ln–MOFs) with ratiometric fluorescent detection and proton conductivity is significant and challenging. Herein, a three-dimensional (3D) Eu–MOF, namely, [Eu4(HL)2(SBA)4(H2O)6]·9H2O, has been hydrothermally synthesized with a dual-ligand strategy, using (4-carboxypiperidyl)-N-methylenephosphonic acid (H3L = H2O3PCH2–NC5H9–COOH) and 4-sulfobenzoic acid monopotassium salt (KHSBA = KO3SC6H4COOH) as organic linkers. Eu–MOF sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 65 publications
1
5
0
Order By: Relevance
“…Consequently, the superior proton conductivity of 1 may be ascribed to the shorter proton transport distances and more abundant proton numbers. The optimal σ value of 1 (1.69 × 10 −4 S cm −1 , at 50 °C and 98% RH) is comparable to many MOFs-based proton conductors, [Eu 4 (HL) 2 (SBA) 4 (H 2 O) 6 ]·9H 2 O (H 3 L = (4-carboxypiperidyl)- N -methylenephosphonic acid, KHSBA = 4-sulfobenzoic acid monopotassium salt, 2.60 × 10 −4 S cm −1 , at 95 °C and 95% RH), 36 (Me 2 NH 2 )(Me 2 NH)[In(mdhbqdc) 2 ] (H 2 mdhbqdc = dimethyl 3,6-dihydroxy-2,5-benzoquinone-1,4-dicarboxylic acid, 2.10 × 10 −4 S cm −1 , at 30 °C under 95% RH). 37 At the same time, the optimal σ value of 2 (3.52 × 10 −6 S cm −1 , at 50 °C and 98% RH) is also comparable to many MOF-based proton conductors, for instance {[Dy 4 (OH) 4 (U) 2 (H 2 O) 8 ]·4.6H 2 O·1.4CH 3 CN} n (2.96 × 10 −6 , at 80 °C, 95% RH), 38 UiO-66-NH 2 (3.5 × 10 −6 S cm −1 , at 80 °C and 98% RH).…”
Section: Resultssupporting
confidence: 63%
“…Consequently, the superior proton conductivity of 1 may be ascribed to the shorter proton transport distances and more abundant proton numbers. The optimal σ value of 1 (1.69 × 10 −4 S cm −1 , at 50 °C and 98% RH) is comparable to many MOFs-based proton conductors, [Eu 4 (HL) 2 (SBA) 4 (H 2 O) 6 ]·9H 2 O (H 3 L = (4-carboxypiperidyl)- N -methylenephosphonic acid, KHSBA = 4-sulfobenzoic acid monopotassium salt, 2.60 × 10 −4 S cm −1 , at 95 °C and 95% RH), 36 (Me 2 NH 2 )(Me 2 NH)[In(mdhbqdc) 2 ] (H 2 mdhbqdc = dimethyl 3,6-dihydroxy-2,5-benzoquinone-1,4-dicarboxylic acid, 2.10 × 10 −4 S cm −1 , at 30 °C under 95% RH). 37 At the same time, the optimal σ value of 2 (3.52 × 10 −6 S cm −1 , at 50 °C and 98% RH) is also comparable to many MOF-based proton conductors, for instance {[Dy 4 (OH) 4 (U) 2 (H 2 O) 8 ]·4.6H 2 O·1.4CH 3 CN} n (2.96 × 10 −6 , at 80 °C, 95% RH), 38 UiO-66-NH 2 (3.5 × 10 −6 S cm −1 , at 80 °C and 98% RH).…”
Section: Resultssupporting
confidence: 63%
“…20 In addition, dual-emission centres can construct ratio-metric fluorescent detection, and the ratio of the intensity at two different wavelengths exhibits a unique colour change under UV. 21 Dual-lanthanide ions (especially Eu 3+ and Tb 3+ ) in Ln-MOFs and emissive guest-doped Ln-MOFs have been applied to detect DPA. However, the guest dopants are unstable and may leach from the framework.…”
Section: Introductionmentioning
confidence: 99%
“…We employed the Stern–Volmer equation I 0 / I = K SV [ Q ] + 1 to further analyze the fluorescence quenching effect, where [ Q ] is the molar concentration of the analyte, K SV is the quenching constant (M –1 ), and I 0 and I represent the luminescence intensity of suspensions of complexes 1 and 2 without and with the addition of the analyte, respectively . The luminescence titration SV curves exhibited linear relationships at lower concentrations but gradually deviated from linearity as the concentration increased, possibly due to the energy transfer process or self-absorption effects. , The quenching constants K SV for 1 toward NFT and NFZ were determined as 5.94 × 10 4 and 6.76 × 10 4 M –1 , respectively, based on the linear segments (Figure S13b,d). Subsequently, utilizing the equation LOD = 3σ/ k , the detection limits (LOD) for 1 toward NFT and NFZ were calculated as 9.75 × 10 –7 and 8.57 × 10 –7 M, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Zuo et al reported a two-dimensional In­(II)-based conductive MOF with an impressive proton conductivity of up to 1.30 × 10 –2 S·cm –1 . Despite the relative success in developing MOF-based proton-conductive materials, research on multifunctional MOFs combining luminescent sensing properties and proton conduction remains limited. To the best of our knowledge, the combination of NFA sensors and proton-conductive MOFs has not been reported. Therefore, the design of functional MOFs with excellent luminescent sensing and proton conduction properties holds great significance in meeting the demands of practical applications.…”
Section: Introductionmentioning
confidence: 99%